Impacto da vacinação contra a Covid-19: uma análise do território piauiense - (:unkn) unknown (Universidade Brasil, 2022)
The behavior of SARS-CoV-2, which causes Covid-19, has challenged world science, however the completion of vaccination against the pathogen has brought the prospect of curbing and controlling the pandemic scenario. The objective was to evaluate the vaccine impact on notifications of Covid-19 in Piauí. This is an exploratory, descriptive and epidemiological study with a quantitative approach, carried out from secondary data available on the public domain website of the state secretary of health of Piauí. The sample comprised all confirmed cases and deaths from Covid-19 notified from January 1 to December 31, 2021. Data collection took place from January to February 2022 and included hospitalizations in clinical, intensive care, stabilization and hospital beds. respirators, new cases, deaths and vaccination records. The results showed stability in the occupation of clinical beds, intensive care units, stabilization units and beds with respirators in the last 14 days of 2021. There was an increase in notifications from January to May 2021 with a greater number of daily cases notified on May 18, indicating 1753 confirmed cases with a decline in cases in June and a downward trend with a variation rate of -39.71%. With regard to deaths resulting from the disease, the highest daily number observed in the state of Piauí occurred on April 11, with 49 deaths. Vaccination recorded a peak of 404,842 vaccine doses dispensed on December 22, with a variation rate of -48.83%. The correlation analysis showed that vaccination is inversely proportional to all hospitalizations and deaths, showing that the higher the vaccination, the lower the hospitalization and deaths from the new Coronavirus, but it did not prevent the transmission of the disease from person to person. Thus, it is necessary that protective measures be maintained and that new studies be carried out in the path of elucidation and genomic surveillance, with a view to persistent immunity and in the immune system escapes to mutations resulting from SARS-CoV-2 infection.
Keywords: Infecção pelo SARS-CoV-2; COVID-19; Vacinação; Engenharia Biomédica (Bioengenharia)